Building fame through tea: the Wu Family and the Manufacture of zisha teapots during the Ming and Qing dynasties - Gao, X; Hein, A (Taylor and Francis, 2024)
By examining the Wu family’s connection with the origin of zisha teapots, this study investigates how Ming literati used material culture to shape family reputation. It unravels the complicated relationship between Ming dynasty literati and the craft products they appreciated. The paper analyzes Ming and Qing dynasty texts discussing the origins of zisha ware as well as material evidence. This study found that the authors of these texts were all connected to the Wu family. This family had success in imperial examinations but wanted to raise their social profile further via their involvement in tea and teaware production and connoisseurship. Their association with the invention of teaware — a story spread via publications by relatives and friends — conveyed the Wu family’s artistic taste. Thus, texts praising tea and tea paraphernalia as well as the exchange of tea gifts became tools for actively creating material culture and establishing influence in literati circles.